AUDIT AS A DECISION-MAKING INSTRUMENT IN INVENTORY MANAGEMENT - Łęgowik-Świącik, Sylwia; Bubel, Dagmara (Advanced Logistic Systems - Theory and Practice, 2016)
In the paper, there has been discussed the issue of the instrumental role of audit in the area of decision-making concerning inventory management. The first part of the paper emphasizes the assessment of audit as a decision-making instrument in inventory management. The considerations presented in the second empirical part constitute the response to the research question. The aim of the paper is to learn and assess dependencies between the audit seen as a decision-making instrument and the efficiency of inventory management in the surveyed company. To respond to the research question there have been presented the results of the empirical research based on the case study. The conclusions from the research indicate that the implementation of the solutions proposed during the audit of inventories determines the efficiency of inventory management in the surveyed enterprise allowing for taking right decisions. In the paper, the authors wish to contribute to the discussion on the extent to which the enterprises of the cement sector in Poland should adapt audit to more efficiently manage production stock which generates high operating costs.